Psychometric properties of the Persian version of Instrument of Professional Attitude for Student Nurses (IPASN) - Mohammad Eghbali; Razieh Bandari; Majideh Heravi‐Karimooi; Fariba Ghaesemzadeh; Ali Montazeri (Wiley, 2021)
Abstract Aim To evaluate nursing students' professionalism attitude, it is necessary to use a validated and reliable instrument. Design This study aimed to develop the Persian version of the eight‐dimensional professionalism attitude questionnaire for student nurses (Instrument of Professional Attitude for Student Nurses). Methods In this cross‐sectional study during March to April 2017, after being translated into Persian and receiving experts' comments face, content, and construct validity of the questionnaire were sought among nursing students. Internal consistency reliability was examined by estimating the Cronbach's alpha coefficient and stability was estimated by calculating intraclass correlation coefficinet. Results A total of 750 students with an average age of 24.15 (SD = 1.32) years participated in the study. Both exploratory and confirmatory factor analyses confirmed the construct of the questionnaire. Cronbach's alpha coefficient for the entire instrument was 0.89 and more than 0.70 for all dimensions. Also the intraclass correlation coefficient for the questionnaire was found to be 0.92, well above acceptable threshold. The findings approved that the Iranian version of Instrument of Professional Attitude for Student Nurses is a reliable and valid questionnaire. Hence, using this questionnaire to conduct studies is recommended.